2004
DOI: 10.1021/jp046854d
|View full text |Cite
|
Sign up to set email alerts
|

Structural Isomers of Dihalosilanones. Theoretical Determination of Their Geometries, Spectroscopic Constants, and Potential Energy Surfaces

Abstract: The geometries and spectroscopic constants of the dihalosilanones, F2SiO, Cl2SiO, Br2SiO, and I2SiO, and their cis- and trans-XSiOX isomers were calculated by high-level computations. The potential energy surfaces of the isomerization reactions were investigated and the transition-state structures determined, together with the isomerization and activation energies and enthalpies. It was shown that, in contrast to silanone and the hydroxysilylenes, the dihalosilanones are much more stable than their other struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Fluorine substitution was also found to play important roles in the relative stabilities of the OSiF 2 and OGeF 2 molecules. 55,67 Recent studies on the reactions of Group 4 metals with BF 3 revealed that the borylene complexes FBMF 2 were formed while the three fluorine transfer products B÷MF 3 were not stabilized. 50 However, when NF 3 and CF 4 were used as reactants, the two fluorine transfer species F 2 CvMF 2 and FNvMF 2 were not stabilized although the FC÷MF 3 and N÷MF 3 molecules with two singly occupied π bonds were formed as the final products.…”
Section: Reactions In the Matrixmentioning
confidence: 99%
“…Fluorine substitution was also found to play important roles in the relative stabilities of the OSiF 2 and OGeF 2 molecules. 55,67 Recent studies on the reactions of Group 4 metals with BF 3 revealed that the borylene complexes FBMF 2 were formed while the three fluorine transfer products B÷MF 3 were not stabilized. 50 However, when NF 3 and CF 4 were used as reactants, the two fluorine transfer species F 2 CvMF 2 and FNvMF 2 were not stabilized although the FC÷MF 3 and N÷MF 3 molecules with two singly occupied π bonds were formed as the final products.…”
Section: Reactions In the Matrixmentioning
confidence: 99%
“…The Si1-O1 bond length (1.568(15) A ˚) is smaller than the Si-O single bond (1.64 A ˚) but longer than the SiQO bond calculated for H 2 Si QO (1.53 A ˚). 27 This may be due to the higher coordination at the silicon. [13][14][15][16] The Si1-O1 bond length is in agreement with those found in compounds with four-coordinate silicon.…”
mentioning
confidence: 99%
“…It corresponds either to the bending frequency in the x-y plane or to the one in the z direction. There exist theoretical investigations of the vibrational properties of silanone, based on ab initio approaches like molecular-orbital theory, Hartree-Fock, configuration interaction, coupled-cluster methods, and others [21][22][23][24][25][26][27]. In these calculations the results vary depending on the method, even sometimes within the same theoretical approach, e.g.…”
Section: Comparison With Experimental Resultsmentioning
confidence: 99%
“…For example, the Si=O stretching frequency has been obtained at 1355 cm −1 by Darling and Schlegel [24], 1182 cm −1 by Gole and Dixon [22], and 1217 cm −1 by Hargittai and Réffy [21], all by using the same expansion into Gaussian functions implemented in GAUSSIAN [28]. Thus, we have compared our results with some of the most recent theoretical values, which are the Gaussian-expansion results using a B3LYP/6-311G(d,p) DFT basis set of Hargittai and Réffy [21], the molecular-orbital theory results using a triple ζ valence basis set at the local DFT level of Gole and Dixon [22], and the coupled cluster method results using a quadruple ζ basis set of Martin [23]. As visible in table 2, the agreement with the theoretical references is very good.…”
Section: Comparison With Experimental Resultsmentioning
confidence: 99%